Analysis of Government Interventions to Addressed Hazard: A Case Study of Covid-19 Pandemic in ASEAN - Rahmat , Siti Rahyla; Hamad Hasul Khan; Firdaus , R.B. Radin; Asyraf , Mohd Noor (International Journal of Membrane Science and Technology, 2023)
This study provides a review of government interventions policies and measures used to address hazard with the case of the COVID-19 pandemic in the Association of Southeast Asia Nations (ASEAN). This study focuses on four government interventions such as policy interventions, social restrictions and lockdown measures, economic interventions, and health policies. Based on the literature reviewed, this study reveals that the lockdown played a crucial role in breaking the COVID-19 pandemic chain. Countries that delayed the implementation of lockdown experienced an increase in the number of COVID-19 cases. On the other hand, countries that proactively hastened the lockdown were able to reduce the number of cases. Furthermore, health and medical facilities such as the availability of Personal Protective Equipment (PPEs), Intensive Care Units (ICUs), and ventilators were important in alleviating the pressure on the health systems. Overall, ASEAN countries initiated similar approaches such as economic stimulus packages, to boost their economies and to minimize the negative economic impact of COVID-19. Generally, all the countries practiced social distancing, wearing of face masks, as well as testing and contact tracing. There were partial and full movement control of the population (lockdowns) as well as closure of international borders educational institutions, and restaurants and entertainment hubs to flatten the pandemic curve and break the COVID-19 chain. This study believes that tester kits were also crucial in detecting earlier cases which probably resulted to the increase in the number of active cases. However, lack of tester kits probably accounted for the understated number of active cases. This study also believes that quarantine zone was more efficient than home quarantine. Although it is now post pandemic, this study is important as a lesson learnt for future mitigation strategy and reduce the impact of hazard.